Cardiac late events in German breast cancer patients: a validation study on the agreement between patient self-reports and information from physicians - Hiltrud Merzenich; Maria Blettner; Dorothea Niehoff; Lukas Schwentner; Marcus Schmidt; Margit Schmitt; Daniel Wollschläger (BMC Cardiovascular Disorders, 2018)
Abstract Background Self-administered health-status questionnaires are important tools in epidemiology. The objective of the presented validation study is to measure the agreement between breast cancer patients’ self-reports and their physicians’ information on late cardiac events, and to investigate determinants of agreement. To estimate possible misclassification is an important requirement for observational studies on cardiovascular endpoints. Methods A retrospective, multi-center cohort study included 11,982 women diagnosed with breast cancer in Germany in 1998–2008. In 2014, a questionnaire survey assessed cardiovascular risk factors and incident cardiac events after therapy. A validation study was conducted, based on a sample of 3091 breast cancer patients from two university hospitals. Among them, 2261 women (73%) sent back the questionnaire on cardiovascular events, and 1316 women gave consent to request medical records from their general practitioners. A total of 1212/1316 (92.1%) medical records could be obtained for validation. Cohen’s kappa coefficient was calculated, and multivariate regression was applied to study the influence of patient characteristics on agreement between both data sources. Results Overall agreement for the composite endpoint of any cardiac event was 84.5% (kappa 0.35). Of 1055 breast cancer patients reporting no cardiac event, 950 (90%) had no such diagnosis in physicians’ medical records. A total of 157 breast cancer survivors indicated a cardiac event, and the same diagnosis was confirmed by GPs for 74 (47%) women. For specific diagnoses, moderate to substantial agreement of self-reports was found for myocardial infarction (kappa 0.54) and stroke (kappa 0.61). Poor to fair agreement was present for angina pectoris, valvular heart disease, arrhythmia, and congestive heart failure. Younger age, higher education and a more recent cancer diagnosis were found to be associated with greater total agreement. Conclusions For the composite endpoint, survivors of breast cancer report the absence of cardiac disease accurately. However, for specific diagnoses, self-reported morbidity data from breast cancer patients may not fully agree with information from physicians. The agreement is moderate for acute events like myocardial infarction and stroke, but poor to fair for chronic diseases.